Pelatihan Pembuatan Hormon Tanaman Berbasis Kearifan Lokal di SMA Negeri 1 Kragan - Ifa Seftia Rakhma Widiyanti; Imas Cintamulya (Universitas Indraprasta PGRI, 2023)
Community service activitiy for the Biology Education study program UNIROW Tuban was carried out at SMA 1 Kragan 1, it was Training on Making Plant Hormones from Organic Materials. Community service activitie Training for Making Plant Hormones Based on Local Wisdom from Organic Materials was carried out at SMA 1 Kragan because they had never made Plant Hormones Based on Local Wisdom from Organic Materials and the raw material for making Plant Hormones Based on Local Wisdom from abundant organic materials, namely Moringa leaves. The timing of the Community Service Implementation in February - March 2021. The community service that was carried out was able to provide several results, including: (1) there was a collaboration between UNIROW and SMA N 1 Kragan. (2) The results of the good responses from the participants based on the results of the questionnaire after the training amounted to 66.67%, the participants were satisfied with the training on making plant hormones based on local wisdom from Moringa leaves because it was in accordance with the expectations of the participants.